Dysphoria mundi: le son du monde qui s'écroule - Preciado, Paul B. (Bernard Grasset, 2022)
«Dysphoria mundi est un texte mutant, qui hybride essai, philosophie, opéra, poésie et autofiction, afin de rendre compte de la transition planétaire en cours. Ce livre apprend au regard à distinguer ce que la propagande nihiliste mainstream cherche à dissimuler : les déplacements irréversibles qui s'opèrent dans les sphères sociales, politiques, sexuelles. Il n'est pas question d'un passé mythique ni d'un avenir messianique, mais d'un présent révolutionnaire. Le XIXe siècle était hystérique ; le XXe, schizophrène ; notre époque est dysphorique. Anxiété généralisée, troubles post-traumatiques, syndrome de dépendance, dysphorie de genre, destruction légitimée de l'écosystème... Voici l'hypothèse que propose ce livre : généraliser la notion de dysphorie afin de la comprendre non pas comme une maladie mentale, mais comme une dissidence politique. L'auteur organise une archive implacable de la fabrication/destruction nécropolitique de la subjectivité dans la modernité, et dessine une cartographie des pratiques d'émancipation susceptibles de transformer l'avenir. On dit souvent qu'il nous est devenu plus facile d'imaginer la fin du monde que de penser la fin du capitalisme. Preciado persiste à observer les preuves de pratiques alternatives à cette impasse : de nouveaux modes de vie jusqu'alors disqualifiés comme improductifs et anormaux se présentent désormais comme la seule issue.»–Page 4 de la couverture.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; LGBTQIA2+; approches et analyses; arts; care; corps; cours; discipline; disphorie; har4600; identités LGBTQIA2+; philosophie; premier cycle; périodes historiques; queer; santé; sciences humaines; sexualité; thématiques; transféminisme; études littéraires

Justice and the politics of difference - Young, Iris Marion; Allen, Danielle S. (Princeton University Press, 2022)
"In this classic work of feminist political thought, Iris Marion Young challenges the prevailing reduction of social justice to distributive justice. The starting point for her critique is the experience and concerns of the new social movements that were created by marginal and excluded groups, including women, African Americans, and American Indians, as well as gays and lesbians. Young argues that by assuming a homogeneous public, democratic theorists fail to consider institutional arrangements for including people not culturally identified with white European male norms. Consequently, theorists do not adequately address the problems of an inclusive participatory framework. Basing her vision of the good society on the culturally plural networks of contemporary urban life, Young makes the case that normative theory and public policy should undermine group-based oppression by affirming rather than suppressing social group differences"
Section: x, 286 pages ; 24 cm.
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; fem9000; inégalités; justice sociale; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Beyond Binary: Genderqueer as Critical Gender Kind - Dembroff, Robin (Philosophers' Imprint, 2020)
We want to know what gender is. But metaphysical approaches to this question solely have focused on the binary gender kinds men and women. By overlooking those who identify outside of the binary–the group I call ‘genderqueer’–we are left without tools for understanding these new and quickly growing gender identifications. This metaphysical gap in turn creates a conceptual lacuna that contributes to systematic misunderstanding of genderqueer persons. In this paper, I argue that to better understand genderqueer identities, we must recognize a new type of gender kind: critical gender kinds, or kinds whose members collectively destabilize one or more pieces of dominant gender ideology. After developing a model of critical gender kinds, I suggest that genderqueer is best modeled as a critical gender kind that destabilizes the ‘binary axis’, or the piece of dominant gender ideology that says that the only possible genders are the binary, discrete, exclusive, and exhaustive kinds men and women.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; hétérosexisme; identités LGBTQIA2+; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sofia; systèmes d'oppressions; thématiques; états-unis

The feminist case against pornography: a review and re-evaluation - Cawston A. (Inquiry (United Kingdom), 2019)
Despite sustained feminist criticism, the production and consumption of pornography does not show signs of waning. Here, I offer a critical review of the existing feminist anti-pornography debate, arguing that it has largely failed to provide suitable grounds for a stable and comprehensive critique, instead often indirectly providing theoretical resources for pornography to reinvent itself. This is a product, in my view, of a misguided focus on the pornographic object. Feminist critics are better served, I argue, by redirecting their critical gaze towards the consumers of pornography, and, in particular, to the attitudes such consumption reflects. To that end, I introduce an alternative, attitudinal approach that enables criticism of pornography as a reflection of sexist attitudes, as well as for its role in concealing these attitudes.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; cours; discipline; philosophie; philosophie politique; pornographie; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; santé; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; éthique

Conceptualiser l’oppression épistémique - Dotson, Kristie (Recherches féministes, 2018)
L’oppression épistémique désigne une exclusion épistémique persistante qui empêche ou limite la contribution d’une personne à la production des savoirs. On hésite à parler d’« oppression épistémique », et cela tient peut-être à la prémisse voulant que les formes épistémiques de l’oppression se ramènent en général à ses formes politiques et sociales. L’auteure convient que de nombreuses formes d’exclusion qui compromettent la capacité d’une personne à contribuer à la production des savoirs peuvent être ramenées à des formes d’oppression politique et sociale, mais il existe néanmoins des formes distinctes et irréductibles d’oppression épistémique. Elle soutient ainsi que la différence fondamentale entre les formes réductibles et irréductibles d’oppression épistémique réside dans le type de résistance à laquelle on fait face dans chaque cas, c’est-à-dire le pouvoir épistémique ou les caractéristiques des systèmes épistémologiques. La distinction entre les formes réductibles et irréductibles d’oppression épistémique permet de mieux comprendre les enjeux que soulève l’emploi de cette expression et la pertinence d’y recourir.
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; invisibilisation; phi4336; philosophie; premier cycle; production des savoirs; pédagogie; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; épistémologie

“Me Too”: Epistemic Injustice and the Struggle for Recognition - Jackson, Debra L. (Feminist Philosophy Quarterly, 2018)
Congdon (2017), Giladi (2018), and McConkey (2004) challenge feminist epistemologists and recognition theorists to come together to analyze epistemic injustice. I take up this challenge by highlighting the failure of recognition in cases of testimonial and hermeneutical injustice experienced by victims of sexual harassment and sexual assault. I offer the #MeToo movement as a case study to demonstrate how the process of mutual recognition makes visible and helps overcome the epistemic injustice suffered by victims of sexual harassment and sexual assault. I argue that in declaring “me too,” the epistemic subject emerges in the context of a polyphonic symphony of victims claiming their status as agents who are able to make sense of their own social experiences and able to convey their knowledge to others.
Keywords: #metoo; 2000 à aujourd'hui; 2010-2019; approches et analyses; corps; cours; cycles supérieurs; discipline; fem9000; harcèlement sexuel; injustices herméneutiques; injustices testimoniales; injustices épistémiques; philosophie; philosophie féministe; périodes historiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; éthique

Living a feminist life - Ahmed, Sara (Duke University Press, 2017)
In Living a Feminist Life Sara Ahmed shows how feminist theory is generated from everyday life and the ordinary experiences of being a feminist at home and at work. Building on legacies of feminist of color scholarship in particular, Ahmed offers a poetic and personal meditation on how feminists become estranged from worlds they critique-often by naming and calling attention to problems-and how feminists learn about worlds from their efforts to transform them. Ahmed also provides her most sustained commentary on the figure of the feminist killjoy introduced in her earlier work while showing how feminists create inventive solutions-such as forming support systems-to survive the shattering experiences of facing the walls of racism and sexism. The killjoy survival kit and killjoy manifesto, with which the book concludes, supply practical tools for how to live a feminist life, thereby strengthening the ties between the inventive creation of feminist theory and living a life that sustains it. https://www.saranahmed.com/
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; afro-féminisme; approches et analyses; care; corps; cours; discipline; fem1000; féminismes noirs; incontournable; intersectionnalité; manifeste; militance; occident; orient; philosophie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; émotions; études culturelles

Luttes féministes autour de la morale sexuelle - Escoda M.R.I.; Praz A.-F.; Lepinard E. (Nouvelles Questions Feministes, 2016)
Keywords: 1900-1999; 2000 à aujourd'hui; 2010-2019; amitié; approches et analyses; asie; cours; discipline; europe; hétérosexisme; phi2030; philosophie; point de vue situé; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques

Disability studies after the ontological turn: a return to the material world and material bodies without a return to essentialism - Feely, Michael (Disability & Society, 2016)
Over recent decades, poststructuralist theories have allowed critical disability scholars to challenge essentialist understandings of the human species and to contest discourses which divide humans into ‘normal’/‘impaired’ subjects with respect to a wide – and ever expanding – range of corporeal and cognitive traits. For critics, however, these theories are deeply flawed. By focusing primarily on language, poststructuralism shifts our critical attention away from the often harsh material realities of life for disabled people. This has led some to turn to critical realism and to effectively re-essentialise impairment. In this article, I wish to consider an alternative approach. I suggest that the recent ‘ontological turn’ in social theory has seen the emergence of new-materialist approaches – including Deleuze and Guattari’s ontology of assemblage and methodology of assemblage analysis – which allow us to consider disability as a material phenomenon without a return to essentialism.
Keywords: 2000 à aujourd'hui; 2010-2019; EDI; approches et analyses; corps; cours; discipline; féminisme matérialiste; histoire et politique; humaines; ontologie; philosophie; post-structuralisme; premier cycle; périodes historiques; ressource en ligne; santé; sciences; sciences humaines; sex1920; thématiques; études critiques du handicap

Des sexes innombrables: le genre à l'épreuve de la biologie - Hoquet, Thierry (Éditions du Seuil, 2016)
Combient y-at-il de sexes? "Deux!", répond l'opinion. "Deux" répond la science. Heureuse concordance : c'est donc que l'opinion a raison, conclura-t-on. Mais est-on si certain que l'opinion et la science disent, sur la question du sexe, la même chose? Quand l'opinion affirme qu'il y a deux sexes, elle soutient qu'il existe, dans chaque espèce, deux types d'individus et seulement deux. Il y aurait alors le masculin et le féminin. Mais quand la science avance qu'il y a deux sexes, que vise-t-elle ? Quelle est, pour un biologiste, la signification des termes "mâle" et "femelle" ? En tentant de compter les sexes, on doit bientôt se risquer à distinguer le normal du pathologique.
Section: 1 vol. (249 p.) : ill., couv. ill. en coul. ; 21 cm.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; corps; cours; discipline; europe; france; phi2030; philosophie; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexe biologique; sexisme; sexualité; systèmes d'oppressions; thématiques

Luttes féministes autour du consentement: Héritages et impensés des mobilisations contemporaines sur la gynécologie - Quéré, Lucile (Nouvelles Questions Féministes, 2016)
L'étude des mobilisations françaises de l'année 2014-2015 autour de la gynécologie permet d'interroger les différentes manières dont les mouvements féministes se sont saisis de la notion de consentement. Théorisé par les féministes à propos de la sexualité, le consentement est apparu comme un des principes fondateurs d'une morale sexuelle féministe. Les mouvements de 2014, portés par des militantes de la cause des femmes, (ré)introduisent cette notion dans le cabinet médical, et l'appliquent notamment à l'interaction gynécologique. Cela leur permet d'utiliser la loi française de 2002 sur les droits des patient·e·s comme un outil de politisation du cabinet gynécologique et de remise en cause des pratiques et des discours des soignant·e·s à l'égard des femmes.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; care; cours; discipline; discours dominant; europe; france; inégalités; justice sociale; militance; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; santé; santé des femmes*; sciences humaines; sexisme; sexualité; systèmes d'oppressions; thématiques

True loves, dark nights: Queer performativity and grieving through music in the work of Rufus Wainwright - Salerno, Stephanie (Université d'État de Bowling Green, 2016)
This dissertation studies the cultural significance of Canadian-American singer/songwriter Rufus Wainwright's (b. 1973) album All Days Are Nights: Songs for Lulu (Decca, 2010). Lulu was written, recorded, and toured in the years surrounding the illness and eventual death of his mother, beloved Quebecoise singer/songwriter Kate McGarrigle. The album, performed as a classical song cycle, stands out amongst Wainwright's musical catalogue as a hybrid composition that mixes classical and popular musical forms and styles. More than merely a collection of songs about death, loss, and personal suffering, Lulu is a vehicle that enabled him to grieve through music. I argue that Wainwright's performativity, as well as the music itself, can be understood as queer, or as that which transgresses traditional or expected boundaries. In this sense, Wainwright's artistic identity and musical trajectory resemble a rhizome, extending in multiple directions and continually expanding to create new paths and outcomes. Instances of queerness reveal themselves in the genre hybridity of the Lulu song cycle, the emotional vulnerability of Wainwright's vocal performance, the deconstruction of gender norms in live performance, and the circulation of affect within the performance space. In this study, I examine the song cycle form, Wainwright's musical score and vocal performance, live performance videos, and fan reactions to live performances in order to identify meaningful moments where Wainwright's musical and performative decisions queer audience expectations. While these musical moments contribute to the already rich and varied lineage of the gay male artist in both classical and popular music, I argue that Wainwright's queer performativity and nontraditional musical choices speak to larger issues important to American culture in the contemporary moment. These issues include the visibility of male public mourning and the healing power of artistic expression in the face of traumatic loss.
https://scholarworks.bgsu.edu/acs_diss/90
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; culture populaire; deuil; discipline; genre; mémoires/thèses; philosophie; périodes historiques; queer; ressource en ligne; résistance; sciences humaines; émotions

Considérations éthiques sur le consentement comme noyau de la sexualité - Viola, F.J.J. (Sexologies, 2015)
La notion de consentement est plus souvent associée aux plaintes pour agression sexuelle qu’aux études et thérapies sexologiques où l’objectif d’une « vie sexuelle satisfaisante » relègue l’idée de contrainte à l’arrière-plan.Dans cet article, nous voulons montrer que, sous l’angle du questionnement sexologique, la notion de consentement recouvre plus que l’accord entre deux personnes quant à un acte ou une relation univoque. Dans la thérapie sexologique, il occupe même une place centrale, tant comme question éthique (qui positionne le thérapeute) que comme contenu de la consultation (comme dessous des plaintes formulées).Une analyse de la littérature médicale fournit des éclairages à l’appui du concept clinique de « consentement pluridimensionnel ». Trois exemples extraits de notre clinique illustrent sa pertinence.Nous suggérons que trois « constantes » soient prises en compte explicitement dans la clinique : la conception du monde, déterminant pour le consultant sa perception d’une « sexualité normale » ; les rapports de pouvoir, s’établissant au sein de tout rapprochement de personnes et la négociation, inévitable perspective pour qu’une quelconque association puisse tenir.L’accès à « une vie sexuelle satisfaisante » passe pour le consultant par l’identification de ce à quoi au juste il a consenti dans le contexte qui fonde sa plainte. Le sexologue l’y aidera par l’attention accordée d’entrée de jeu à ces trois constantes qui forment la charpente du consentement.
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; approches et analyses; canada; consentement; corps; cours; discipline; phi2030; philosophie; premier cycle; périodes historiques; rapports de pouvoir; régions géographiques; sciences humaines; sexualité; thématiques

Race, racisme, discriminations: anthologie de textes fondamentaux - Bessone, Magali; Sabbagh, Daniel (Hermann, 2015)
« La race n'est-elle qu'une chimère - une fiction collective aux effets pernicieux - ou est-elle un concept nécessaire à l'analyse et à l'éradication éventuelle du racisme et de ses conséquences? Cette catégorie ambiguë relève-t-elle de la biologie ou bien renvoie-t-elle à une réalité de nature socio-politique? Le racisme est-il d'abord un attribut des individus ou des institutions - un état mental fait de croyances et d'affects ou un système social? Toute discrimination raciale est-elle inévitablement raciste? Est-elle immorale et injuste même dans les cas où elle ne serait pas entièrement irrationnelle? Enfin, la discrimination positive est-elle justifiable? Telles sont quelques-unes des questions abordées dans ce recueil, qui propose une introduction au champ d'investigation que la race, le racisme et les discriminations constituent pour la philosophie - ici envisagée dans son articulation avec les sciences sociales. Il réunit dix textes majeurs, presque tous inédits en français. »
Section: 372 pages ; 23 cm.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; antiracisme; approches et analyses; cours; discipline; discriminations; europe; occident; phi4336; philosophie; premier cycle; privilèges; périodes historiques; racisme; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; violences

Rôle des valeurs en science: contributions de la philosophie féministe des sciences - Ruphy, Stéphanie (Écologie & politique, 2015)
Cinq décennies d’études féministes sur les sciences ont renouvelé et enrichi significativement les réflexions épistémologiques sur des notions fondamentales comme celles d’objectivité ou de preuve empirique, et plus largement sur la question du rôle des valeurs en science. Nous présentons quelques-unes des positions féministes actuelles les plus influentes au sein de la philosophie des sciences contemporaine, positions qui offrent des alternatives à l’idéal de neutralité de la science et ouvrent la possibilité d’une pratique proprement féministe des sciences. Nous discuterons également du tournant politique de la philosophie des sciences, invitée à se saisir de la question du rôle et des objectifs assignables à la science dans nos démocraties contemporaines.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; approches et analyses; cours; discipline; discours dominant; europe; france; phi4336; philosophie; point de vue situé; premier cycle; pédagogie; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; épistémologie

Engels, Friedrich. « La famille monogamique, ou la grande défaite historique du sexe féminin » dans Philosophie de la famille : communauté, normes et pouvoirs - Radica, Gabrielle (Philosophie de la famille: communauté, normes et pouvoirs, 2013)
Aucune pensée psychologique, morale, sociale, juridique ou politique ne peut faire l’économie d’une étude de la famille, quand bien même elle adopterait des positions individualistes ou libérales. Or quand il s’agit de la famille, l’effort de définition se lie immanquablement à une réflexion normative, car nul ne se contente de dire ce qu’est la famille et chacun croit savoir ce qu’elle devrait être. Les textes cités dans ce recueil, qu’ils proviennent de la philosophie classique (Aristote, Rousseau, Diderot, Kant, Hegel), contemporaine (Okin, Walzer), ou encore de représentants des sciences humaines (Durkheim, Freud, Lenoir, Donzelot), témoignent de ce entrelacement et le questionnent. Que la famille soit considérée comme la plus naturelle des unions, comme une violence faite à la nature, ou comme une construction sociale; qu’elle soit définie comme une société contractuelle ou comme une communauté transcendant l’existence de ses membres : tout cela commande qu’on détermine si cette institution est nécessaire, oppressive et essentiellement hiérarchique, ou si elle peut favoriser certaines formes de liberté et d’égalité; et qu’on dise quels pouvoirs elle subit à son tour et quelle justice elle appelle.
Section: 1 vol. (357 p.) ; 18 cm.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; care; corps; cours; discipline; discours dominant; europe; famille; france; hétérosexualité; mariage; maternité; patriarcat; phi2030; philosophie; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques

Young, Black and male : Exploring the intersections of racial and gender identity in an all-Black male high school - Rogers, Leoandra Onnie (New York University, 2012)
From popular culture to academia, there is national panic about the dismal life trajectories of Black males. This "Black male crisis" has contributed to emergent all-Black, all-male schools. Racial identity is commonly used to explain underperformance among Blacks, yet within-group gender disparity signifies the importance of gender relative to race. Minimal research exists on Black males' gender identities, and less on the intersections of gender and race. This longitudinal dissertation used quantitative and qualitative data to examine the development and intersections of racial and gender identity among Black adolescent males transitioning from co-educational grammar schools and entering the ninth grade at an all-Black, all-male high school. Findings are presented in two empirical papers. Paper 1 examined survey data collected from Black males (N = 183) to explain how boys' racial and gender identities were interrelated, changed over time, and influenced their psychological and academic adjustment. Results from the growth curve analysis revealed that boys' racial and gender identities were interrelated with each other and that higher levels of identity attachment were associated with better psychological and academic adjustment. Moreover, the strength of the relationship between gender identity and psychological adjustment increased over time, indicating that gender identity became increasingly important for boys' wellbeing. Paper 2 analyzed interview data with a subsample of Black males (n = 21) to examine how they resisted and accommodated racial and gender stereotypes. Results from the qualitative analysis revealed that boys were aware of the ways that racial and gender stereotypes overlap, but they responded to these stereotypes in different ways. Although some boys accommodated to both racial and gender stereotypes and others resisted these stereotypes, the majority of the boys responded by accommodating to gender stereotypes and resisting racial stereotypes. That is, they tended to perpetuate cultural stereotypes that require males to be the leader, emotionally stoic, and not to be feminine (i.e., gay) while challenging beliefs about the intellectual inferiority and incompetence of Black people. Findings are interpreted within the macro-context of cultural stereotypes and the micro-context of an all-Black male school. Implications for the study of identity, Black males, and single-sex education are discussed.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; adolescence; amériques; approches et analyses; chicago; discipline; genre; hommes* noirs; identité raciale; intersectionnalité; mémoires/thèses; philosophie; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; stéréotypes; étude longitudinale; étude qualitative; étude quantitative

Gabriel Girard – Interview Elsa Dorlin : Le Queer est un matérialisme - Girard, Gabriel (Syllepse, 2007)
Interview d'Elsa Dorlin pour l'ouvrage "Femmes, genre, féminismes".
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; amériques; approches et analyses; cours; discipline; europe; france; féminisme matérialiste; histoire et politique; philosophie; philosophie politique; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; soc2014; thématiques; états-unis